Complete polynmial vector fileds in Euclidean ball - N.M. ben YOUNSIF, N.M. ben YOUNSIF (مجلة العلوم الإنسانية والتطبيقية, 2023)
في هذه الورقة نواصل عملنا على complete polynomial vector field in the unit ball of a Euclidean space بواسطة النظرية 2-4